Work-family Conflict and Psychological Stress among Nurses in Irbid Hospitals - Al-jobour, Feras Qurit’e; Al-jarrah, Esraa Mohammed (Dirasat: Educational Sciences, 2022)
Objectives: This study aimed to investigate the relationship between work-family conflict and psychological stress among Nurses working in Irbid hospitals, in Jordan. Methods: The study relied on the correlational descriptive approach. The study sample consisted of (730) nurses who were selected using the convenience sampling method. To achieve the objectives of the study, two scales were developed. The first scale was to measure work-family conflict, and the other scale was to measure psychological stress, the validity and stability of both scales were verified. Results: The results showed that both levels of work-family conflict and psychological stress were (high). Moreover, there was a significant positive relationship between work-family conflict and psychological stress among participants. The results also showed that there were statistically significant differences in the level of work-family conflict due to the variables (marital status, number of family members, and the department), and there were statistically significant differences in the level of psychological stress due to the variables (marital status, and the department). Conclusions: Based on the results above, it was recommended to improve the financial and psychological support provided to nurses, in order to enable them to confront the influences of work-family conflict. And providing family and vocational counseling programs for nurses, to help them to cope with psychological stress caused by work-family conflict.